THE IMPACT OF ENVIRONMENTAL CHANGES AFTER MERAPI ERUPTION 2010 TOWARD THE IMAGE OF TOURISM - Rindrasih, Erda (JURNAL NASIONAL PARIWISATA, 2013)
In the end of 2010, the Merapi Volcano erupted and resulted some problems and changes from physical and civilization changes impact to the economic and its image. The Merapi volcano is seen as the mountain ecosystem that has specific character. Besides its popularity as the most active volcanoes in the world and the uniqueness of its eruption pattern, the Merapi volcano is one of the most important geomorphologies to support the life of civilization through its natural resource such as water, land, spring and oxygen.Â The last eruption of Merapi volcano is characterized with multi-eruption from 26 October to 11 November 2010. Merapi threw pyroclastic material and hot clouds that could destroy the settlement, facilities, and infrastructure and buried the river. It destroyed the Kinahrejo village and the material sedimented three rivers that are Kuning, Gendol and Woro. Besides that, this catastrophic disaster killed 300 people, thousands of livestock, destroy hundreds of houses, hundred hectare of paddy field and agricultural field. Moreover, it also destroy the civilization by forcing people to move from their place of life. In addition, the Merapi has been leaving both positive and negative image of Yogyakarta of course as a result of the media publication and broadcasting.Â The aims of this paper is to analyses the environments and images changes as result of Merapi volcano eruption. The environmental changes have been captured from two factors: first, the number of damaged land area and dangerous area and second from the condition of water. Moreover, the images changes have been captured from the image Yogyakarta tourism destination. The method of the study is a combination between qualitative and qualitative approach. The data used the secondary report from previous study and primary data from in-depth interview with 30 foreign visitors. The result of the study shows that: first, the pattern of the lava flow is relatively similar to the previous pattern, second, water aquifer is not changed but locally changes its quality of water. In term of image from the visitors the study shows that visitor tend to wait until the condition of Merapi get better before they visit Yogyakarta.Â